(untitled) (Veterinary Science, 2026)
During 2025, the Azul Laboratory received a total of 68 aborted bovine foetuses from different herds in the Province of Buenos Aires for etiological diagnosis. In 7 of them, originated from the districts of Alvear, Lamadrid, Benito Juárez, Ayacucho, and Tapalqué, Brucella spp. was detected and isolated from abomasal fluid and lung samples. Initial detection was performed using direct immunofluorescence and Stamp staining, followed by culture on selective media. The isolates were sent to the Brucellosis Department of SENASA, where they were confirmed by biochemical tests and multiplex PCR as belonging to Brucella abortus biovar 1 field strains, ruling out the involvement of the vaccine strains S19 and RB51. These findings demonstrate the active circulation of B. abortus in breeding herds in the Pampas region, despite the implementation of the National Control and Eradication Plan